UNUSUAL CASE OF A METAL FOREIGN OBJECT IN ORBITOCRANIAL INJURY: UNLOCKING THE MACCARTY KEYHOLE - Rahman, Fadiah Gazzani; Pratiwi, Andi; Halimah Pagarra; Suliati P. Amir (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2025)
Introduction. Penetrating orbitocranial injuries are quite rare but very fatal if left untreated. Various metal objects have been reported as foreign bodies that have penetrated the orbit. However, unusual objects such as motorcycle locks have never been reported before. Case Illustration. A 14-year-old boy was brought to the emergency room with a motorcycle lock embedded in his left temporal region. Examination of the left eye showed decreased vision, clear serous ciliary secretions, conjunctival hyperemia, chemosis, and relative afferent pupillary defect. Investigations using a 3D Head MSCT Scan revealed the presence of a metal object that penetrates the left optic nerve, the rectus lateralis muscle, and the frontal process of the left zygoma bone in the left temporal region, which is located around the MacCarty keyhole. The operation in the form of exploration and foreign object removal was then carried out in collaboration with the neurosurgeon. No postoperative complications were reported, but the patient had restricted movement of the left eye. Discussion. Penetrating orbitocranial injury should be treated as an emergency. Diagnosis should include comprehensive ophthalmological and neurological examinations. CT Scan continues to be the best cranial imaging technique. In this case, the motorcycle lock penetration was around the MacCarty keyhole, a structure that is frequently used to enter both the orbit and the frontal fossa, which located 7 mm superior and 5 mm posterior to the frontozygomatic suture. An appropriate surgical strategy is mandatory for removing the object because it may lead to serious consequences, including cerebral, infectious, vascular complications, and even death. Conclusion. Metal foreign objects such as motorcycle lock was considered unusual, particulary when it unlock an important landmark such as MacCarty keyhole. This case emphasizes the significance of a surgical strategy based on accurate anatomical tracking.